2016
DOI: 10.1002/gcc.22365
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐cancer analysis of copy number changes in programmed death‐ligand 1 (PD‐L1, CD274) – associations with gene expression, mutational load, and survival

Abstract: Inhibition of the PD-L1 (CD274) - PD-1 axis has emerged as a powerful cancer therapy that prevents evasion of tumor cells from the immune system. While immunohistochemical detection of PD-L1 was introduced as a predictive biomarker with variable power, much less is known about copy number alterations (CNA) affecting PD-L1 and their associations with expression levels, mutational load, and survival. To gain insight, we employed The Cancer Genome Atlas (TCGA) datasets to comprehensively analyze 22 major cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 59 publications
3
81
0
1
Order By: Relevance
“…Although future studies are needed to further establish robust and reliable determinants of response to ICI (Carbognin et al 2015; Patel and Kurzrock 2015), PDL1 amplification might serve as a rapidly available and inexpensive surrogate marker across histologic entities, as supported by the striking therapeutic activity of PD1 blockade in TNBC (this study) and refractory classical Hodgkin lymphoma (Ansell et al 2015; Roemer et al 2016) characterized by Chromosome 9p24.1 gain. In a recent pan-cancer analysis, PDL1 gains were shown to occur in many cancer types and to result in PDL1 mRNA overexpression in some tumors (Budczies et al 2016). Moreover, a PDL1 core amplification region of 7.8 Mb on Chromosome 9p that extended to the telomere was identified, consistent with the finding in this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although future studies are needed to further establish robust and reliable determinants of response to ICI (Carbognin et al 2015; Patel and Kurzrock 2015), PDL1 amplification might serve as a rapidly available and inexpensive surrogate marker across histologic entities, as supported by the striking therapeutic activity of PD1 blockade in TNBC (this study) and refractory classical Hodgkin lymphoma (Ansell et al 2015; Roemer et al 2016) characterized by Chromosome 9p24.1 gain. In a recent pan-cancer analysis, PDL1 gains were shown to occur in many cancer types and to result in PDL1 mRNA overexpression in some tumors (Budczies et al 2016). Moreover, a PDL1 core amplification region of 7.8 Mb on Chromosome 9p that extended to the telomere was identified, consistent with the finding in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer data sets (study brca_tcga_pub2015) including data on DNA copy number status (GISTIC) and mRNA expression (RNA Seq V2 RSEM) of PDL1 were retrieved from the cBioPortal for Cancer Genomics () and analyzed as described previously (Budczies et al 2016). Immunohistochemistry data for ER, PR, and HER2 as well as FISH data for HER2 were retrieved from the TCGA data portal ().…”
Section: Methodsmentioning
confidence: 99%
“…Genomic rearrangements of PD-L1 have also been described in primary mediastinal large Bcell lymphomas [22]. A recent comprehensive survey of Budczies et al [15] revealed frequent PD-L1 copy number variations (gains and amplifications [12%], deletions [31%]) across different cancer subtypes with direct impact on its protein and mRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Přítomnost MSI je také významným prediktorem při terapii kolorektálních karcinomů pomocí checkpoint inhibitorů, terapeutických protilátek blokujících povrchové molekuly PD-1 a PD-L1 [29][30][31]. Vzhledem k tomu, že použití checkpoint inhibitorů přineslo v posledních letech významný posun v léčbě celé řady nádorových onemocnění, zvažuje se jejich využití i pro terapii ovariálních karcinomů [32,33]. Detekce poruch MMR a MSI by se tak v budoucnu mohla stát jedním z důležitých prediktivních markerů pro terapii využívající checkpoint inhibitory.…”
Section: Arid1aunclassified